Predicting the Risk for Pathological Fracture in Bone Metastases. - Altsitzioglou, Pavlos; Tsukamoto, Shinji; Errani, Costantino; Tanaka, Yasuhito; Mavrogenis, Andreas F. (Current Oncology, 2025)
Approximately 50–70% of patients with advanced cancer will experience bone metastases. The link between metastatic lesions and pathological bones is especially troubling since more metastases mean a higher chance of painful fractures, which can reduce mobility and often require surgery. Therefore, fracture risk predictions are essential for managing patients with bone metastases. However, the current methods for evaluating the risk of fractures are subjective, with low predictive value. This paper highlights how there being no effective comprehensive models for grouping patients by fracture risk due to skeletal metastases makes it harder to create personalized treatment plans; presents the methods currently used for objective evaluations of the pathological fracture risk in bone metastases; and discusses their pros and cons.